Beispiel Nr: 03
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 9 x -2 y =5\\ 5 x -2 y = 1 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 9 x -2 y =5\\ II \qquad 5 x -2 y = 1 \\ \text{I nach y auflösen}\\ 9 x -2 y =5 \\ 9 x -2 y =5 \qquad /-9 x\\ -2 y =5 -9 x \qquad /:\left(-2\right) \\ y =-2\frac{1}{2} +4\frac{1}{2} x \\ \text{II nach y auflösen}\\ 5 x -2 y =1 \\ 5 x -2 y =1 \qquad /-5 x\\ -2 y =1 -5 x \qquad /:\left(-2\right) \\ y =-\frac{1}{2} +2\frac{1}{2} x \\ \text{I = II}\\ -2\frac{1}{2} +4\frac{1}{2} x =-\frac{1}{2} +2\frac{1}{2} x \qquad /-4\frac{1}{2} x /+\frac{1}{2} \\ -2\frac{1}{2}+\frac{1}{2} =2\frac{1}{2} x -4\frac{1}{2} x \\ -2 =-2 x \qquad /:\left(-2\right) \\ x=1 \\ \text{x in I}\\ y =-2\frac{1}{2} +4\frac{1}{2} \cdot 1 \\ y=2 \\ L=\{1/2\} \end{array} & \begin{array}{l} I \qquad 9 x -2 y =5\\ II \qquad 5 x -2 y = 1 \\ \text{I nach x auflösen}\\ 9 x -2 y =5 \\ 9 x -2 y =5 \qquad /+2 y\\ 9 x =5 +2 y \qquad /:9 \\ x =\frac{5}{9} +\frac{2}{9} y \\ \text{II nach x auflösen}\\ 5 x -2 y =1 \\ 5 x -2 y =1 \qquad /+2 y\\ 5 x =1 +2 y \qquad /:5 \\ x =\frac{1}{5} +\frac{2}{5} y \\ \text{I = II}\\ \frac{5}{9} +\frac{2}{9} y =\frac{1}{5} +\frac{2}{5} y \qquad /-\frac{2}{9} y /-\frac{1}{5} \\ \frac{5}{9}-\frac{1}{5} =\frac{2}{5} y -\frac{2}{9} y \\ \frac{16}{45} =\frac{8}{45} y \qquad /:\frac{8}{45} \\ y=2 \\ \text{y in I}\\ x =\frac{5}{9} +\frac{2}{9} \cdot 2 \\ x=1 \\ L=\{1/2\} \end{array} \end{array} $